In vivo hypocholesterolemic effect of MARDI fermented red yeast rice water extract in high cholesterol diet fed mice - Yeap, Swee Keong; Beh, Boon Kee; Kong, Joan; Ho, Wan Yong; Mohd Yusof, Hamidah; Mohamad, Nurul Elyani; Hussin, Aminuddin; Jaganath, Indu Bala; Mohamed Alitheen, Noorjahan Banu; Jamaluddin, Anisah; Long, Kamariah (Hindawi Publishing Corporation, 2014)
Fermented red yeast rice has been traditionally consumed as medication in Asian cuisine. This study aimed to determine the in vivo hypocholesterolemic and antioxidant effects of fermented red yeast rice water extract produced using Malaysian Agricultural Research and Development Institute (MARDI) Monascus purpureus strains in mice fed with high cholesterol diet. Absence of monacolin-k, lower level of γ-aminobutyric acid (GABA), higher content of total amino acids, and antioxidant activities were detected in MARDI fermented red yeast rice water extract (MFRYR). In vivo MFRYR treatment on hypercholesterolemic mice recorded similar lipid lowering effect as commercial red yeast rice extract (CRYR) as it helps to reduce the elevated serum liver enzyme and increased the antioxidant levels in liver. This effect was also associated with the upregulation of apolipoproteins-E and inhibition of Von Willebrand factor expression. In summary, MFRYR enriched in antioxidant and amino acid without monacolin-k showed similar hypocholesterolemic effect as CRYR that was rich in monacolin-k and GABA.